EFFECT OF SHORT-TERM CAFFEINE SUPPLEMENTATION ON STRESS RESPONSE AND IMMUNE SYSTEM OF MALE ATHLETES - Tofighi, Asghar; Ameghani, Akram; Jamali, Ali; Qarakhanlou, Bahram Jamali (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Vigorous exercise stress might be leading cause of immune system disorders and appearance of acute and chronic inflammation in human body. Caffeine supplementation prior to exercise can be effective on body immune response. This study aimed to evaluate the effect of short-term caffeine supplementation on immune response and stress index in male athletes after an exhaustive aerobic exercise. Materials and methods : In a double-blind study 24 male athletes (endurance runner and triathlon) randomly divided in Caffeine supplementation (CAF) and Placebo (CON) groups. One hour prior to main exhaustive treadmill test (Bruce test) CAF group consumed caffeine (6 Mg/BW) and CON group received placebo. Blood samples were collected before and immediately after exercise test from anticubital vein. After supplying serum; Cortisol, leukocyte and serum Heat shock protein 72 (Hsp72) concentrations were determined using ELISA method. Paired and independent t student test was used for analysis of inter and intra group differences respectively. Results: serum cortisol and Hsp72 concentrations in CON group was significantly higher than CAF group (P<0.05), However serum leukocyte changes was not statistically significant (P>0.05). In addition Mean of variation in CON group was significantly higher than CAF group (P<0.05). Conclusions: Based on study results caffeine supplementation prior to short-term exhaustive aerobic exercise has positive effect on innate immunity and body defensive system.